2019
DOI: 10.1111/joor.12865
|View full text |Cite
|
Sign up to set email alerts
|

Jaw‐neck movement integration in 6‐year‐old children differs from that of adults

Abstract: Background A functional integration between the jaw and neck regions during purposive jaw movements is well described in adults, but there is a lack of knowledge of such integration during jaw function in children. Objectives To determine the movement integration between the jaw and neck during jaw motor tasks in 6‐year‐olds, whether there is a difference between children and adults. Methods Jaw and neck movements were recorded with an optoelectronic 3D system in 25 healthy 6‐year‐olds (12 girls, 13 boys) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 51 publications
1
9
1
Order By: Relevance
“…6,31 When comparing jaw opening-closing and chewing tasks in the present study, the jaw-neck integration was task dependent for both children and adults. Larger head movement amplitudes during maximal jaw opening-closing tasks, compared to chewing, were previously reported for 6-year-old children and adults, 19 and were confirmed here in a longitudinal study design. In a developmental perspective, a strong functional linkage between the jaw and neck motor systems could be an efficient prerequisite that optimises the jaw opening ability and positioning of the gape to achieve specific skills in oral activities such as eating and speech behaviour.…”
Section: Ratio Between Head-jaw Movement Amplitudessupporting
confidence: 90%
See 1 more Smart Citation
“…6,31 When comparing jaw opening-closing and chewing tasks in the present study, the jaw-neck integration was task dependent for both children and adults. Larger head movement amplitudes during maximal jaw opening-closing tasks, compared to chewing, were previously reported for 6-year-old children and adults, 19 and were confirmed here in a longitudinal study design. In a developmental perspective, a strong functional linkage between the jaw and neck motor systems could be an efficient prerequisite that optimises the jaw opening ability and positioning of the gape to achieve specific skills in oral activities such as eating and speech behaviour.…”
Section: Ratio Between Head-jaw Movement Amplitudessupporting
confidence: 90%
“…Two studies on early childhood, 4-7 18 and 6 years of age, 19 observed that jaw opening-closing was accompanied by simultaneous neck extension-flexion. Moreover, the children typically displayed large variability in the jaw and head-neck movements.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…In the present study of jaw‐neck function, the findings of smaller jaw amplitudes but no change in head amplitudes may seem contradictory. However, during natural jaw function, although the head movement is proportional to the jaw movement, head movement is considerably smaller, normally with a ratio between head and jaw movements of about 10%‐20% during maximal jaw opening 1,50 . This means, that during the jaw opening‐closing task performed in our study, the magnitude of head movements is considerably smaller than the movements performed during the maximal range of cervical movements examined by Sterling et al 47 and Fernandez‐Perez et al 46 in acute whiplash populations.…”
Section: Discussioncontrasting
confidence: 47%
“…In addition to TMDs, jaw movements were reported to have a close relationship with cervical muscles, even the body balance [ 63 , 64 ]. To the authors’ limited knowledge, though there are studies about the influences of dental occlusion on body balance [ 63 ], studies about denture occlusion and body balance are still scarce.…”
Section: Final Discussionmentioning
confidence: 99%